RISIKO SISTEMATIS DAN LEVERAGE TERHADAP HARGA SAHAM SUBSEKTOR PROPERTY DAN REAL ESTATE YANG LISTING DI BEI - -, NURHIDAYAH -; -, MARTA WINDAYANTI (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstrack : This researchaimed todetermine the effect ofsystematic riskand leverage simultaneously and partiallyto the stock priceon theproperty and real estate sub-sectors listed onthe Indonesia Stock Exchange quarterly period March 2008 -June 2012 and to determine the effect ofdominant between systematic risk and leverage to the stock priceon theproperty and real estatesub-sectorslisted on the Indonesia Stock Exchange quarterly periodperiod March 2008 -June 2012. That of the 3 companies listed only PT. Ciputra Property Tbk, PT. Lippo Karawaci Tbk, dan PT. Pakuwon Jati Tbk.wo pass the test. Analysis of the data is multiple linear regression for hypotheses I, II and III as well as different test paired T-test.The results of multiple linear regression analysis showed that the systematic risk o fleverage and significant effect on stock prices (hypotheses I). DAR and DER is partially variables significantly influence stock prices (hypothesis II). Degree Of Financial Leverage is a dominant variable influence on stock prices (hypothesis III). The results of different test Pairedt-test showed that there is a difference between the stock price withits intrinsic value to obtain the value of the undervalued and overvalued comparison. Key words: systematic risk, leverage, stock price.